Effectiveness of BP4 in Preventing Early Marriage in 2023 (Case Study at the Religious Affairs Office of Labuhan Deli District) - Tarigan, Aditia Taruna; Irwan, Irwan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to see the effectiveness of BP4 (Marriage Advisory, Development, and Preservation Agency) at the Labuhan Deli District Religious Affairs Office in terms of preventing marriage at an early age in Labuhan Deli District. This research uses two problem formulations, namely what is the role and function of BP4 (Advisory, Development, and Preservation of Marriage) in the Office of Religious Affairs, and what is the effectiveness of BP4 (Advisory, Development, and Preservation of Marriage)? at KUA Labuhan Deli District in preventing marriage at an early age in Labuhan Deli District. This research includes qualitative research with empirical juridical research methods and uses two data sources, namely primary data sources and secondary data sources. The results of this research show that in 2023 there will be 40% of brides who marry under the age of 21. This shows that the role of BP4 counselors in preventing marriage at an early age is not yet effective because there are still many brides who marry under the age of 21, however, compared to the previous year, there has been a decrease in the number of early marriages, namely in 2022, in which year the number of early marriages reached 50. The KUA of Labuhan Deli District has tried its best to provide outreach on preventing marriage at an early age, but there are still internal and external obstacles that are obstacles to the effective implementation of preventing marriage at an early age.